Frog occupancy of polluted wetlands in urban landscapes. Issue 2 (27th November 2018) - Sievers, Michael; Hale, Robin; Swearer, Stephen E.; Parris, Kirsten M.
Abstract: Urban sprawl and the rising popularity of water‐sensitive urban design of urban landscapes has led to a global surge in the number of wetlands constructed to collect and treat stormwater runoff in cities. However, contaminants, such as heavy metals and pesticides, in stormwater adversely affect the survival, growth, and reproduction of animals inhabiting these wetlands. A key question is whether wildlife can identify and avoid highly polluted wetlands. We investigated whether pond‐breeding frogs are attempting to breed in wetlands that affect the fitness of their offspring across 67 urban wetlands in Melbourne, Australia. Frog species richness and the concentration of contaminants (heavy metals and pesticides) were not significantly related, even in the most polluted wetlands. The proportion of fringing vegetation at a wetland had the greatest positive influence on the number of frog species present and the probability of occurrence of individual species, indicating that frogs inhabited wetlands with abundant vegetation, regardless of their pollution status. These wetlands contained contaminant levels similar to urban wetlands around the world at levels that reduce larval amphibian survival. These results are, thus, likely generalizable to other areas, suggesting that urban managers could inadvertently be creating ecological traps in countless cities. Wetlands are important tools for the management of urban stormwater runoff, but their construction should not facilitate declines in wetland‐dependent urban wildlife. Abstract : Article impact statement : That contaminated urban wetlands are readily occupied by frogs has implications for conservation.